From classroom training to e-learning: a journey through the quality of learning life of nurse students in post-graduate education - A longitudinal qualitative study - Sarli, Leopoldo; Artioli, Giovanna; Bogotto, Sonia; Labelli, Elsa; Pittella, Francesco; Guasconi, Massimo; De Simone, Rosangela; De Luca, Enrico; Rossi, Sandra; D'Apice, Clelia (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: recent studies regarding COVID-19 experiences of nursing students highlighted the effect of the transition from face-to-face to online education, rather than the complexity of the overall quality of educational life. This study aim investigating of how the students perceive the quality of educational life in the forced online training, searching for any shift of meanings concerning the students learning experience, from the first phase of the sudden transition to online and the online stabilization phase.Methods: a longitudinal qualitative study, carried during two moments of the online teaching activity forced by COVID-19, the first one in May-June 2020 and the second six months later in January -February 2021. A convenience sample of 24 students attending post-graduate courses for health professions recruited at University of Parma, answered in-depth interviews, videotaped, verbatim transcribed and analyzed using the Braun and Clarke model.Results: five themes emerged from meaning shift of data collection: reactions to change in educational life; factors favoring a new quality of educational life; factors hindering the perception of the quality of educational life; adaptation strategies to the new educational life; tools and strategies to facilitate communication and the absence of the classroom.Conclusions: participants perceive advantages of online teaching, on quality of their educational life. The issue of how to create opportunities for internship period remains open. Further research to understand online internship and exploring what extent it is essential to propose it in face-to-face modality.